The Mutual Intelligibility of the Tunisian, Algerian, and Egyptian Dialects - Ben Hazem, Lynda (Linguistik, Terjemahan, Sastra (LINGTERSA), 2025)
Whether in Asia or the West, most people view all Arab countries as a single group “the Arab world.” Few realize that the Arab world spans over two major regions: the Middle East and North Africa. Even fewer are aware of the differences between these two areas or the distinctions among individual countries within them. These differences are not only of a religious or legislative nature, but also linguistic and communicative. Much like people from different provinces in China, Arabs from different countries often face communication issues with fellow Arabs from abroad. However, research on the dialects of various Arab countries is quite limited and mostly centered on the Middle East. This study focuses on three North African countries—two of which belong to the Maghreb.